1994
DOI: 10.1017/s1041610294001602
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Abilities Screening Instrument (CASI): A Practical Test for Cross-Cultural Epidemiological Studies of Dementia

Abstract: The Cognitive Abilities Screening Instrument (CASI) has a score range of 0 to 100 and provides quantitative assessment on attention, concentration, orientation, short-term memory, long-term memory, language abilities, visual construction, list-generating fluency, abstraction, and judgment. Scores of the Mini-Mental State Examination, the Modified Mini-Mental State Test, and the Hasegawa Dementia Screening Scale can also be estimated from subsets of the CASI items. Pilot testing conducted in Japan and in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
653
2
7

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 806 publications
(664 citation statements)
references
References 4 publications
2
653
2
7
Order By: Relevance
“…Functionally, they appeared better able to walk but had lower grip strength. There was no difference in cognitive score (43).…”
Section: Resultsmentioning
confidence: 72%
“…Functionally, they appeared better able to walk but had lower grip strength. There was no difference in cognitive score (43).…”
Section: Resultsmentioning
confidence: 72%
“…In brief, all subjects were first screened with the CASI (Teng et al, 1994), a measure of global cognitive function. Then those who met screen positive criteria were further examined, including a proxy interview, neuropsychological testing based on the CERAD battery (Morris et al, 1989), a neurological exam, and neuroimaging.…”
Section: Subjects and Image Acquisitionmentioning
confidence: 99%
“…On his first visit in 2005, his Mini-mental State Examination (MMSE) (Folstein et al 1975) score was 21/30 and his Cognitive Ability Screening Instrument (CASI) (Teng et al 1994) score was 69/100, with deficits on the items of recent memory and verbal fluency. His cerebral blood flow study by HMPAO-SPECT showed hypo-perfusion in the frontal lobes in addition to temporal and parietal lobes.…”
Section: Presentation Of Patients and Clinical Settings Patient A: Anmentioning
confidence: 99%